DESIGNING A SPECIALIZED AUDITORIUM AS A CENTRAL VENUE FOR APPLIED STUDIES AND RESEARCH IN PRECISION AGRICULTURE - Atanasov, Asparuh; Bankova, Aleksandrina (Innovation in Woodworking Industry and Engineering design, 2024)
The present paper focuses exclusively on the establishment of a Centre for Precision Agriculture (CPA) – a specialized facility tailored specifically for training, lectures, laboratory exercises and seminars. The project itself involves the transformation of the existing auditorium into a modern venue for applied studies and scientific research at Dobrudja College of Technology, geared towards the implementation of innovations in the field of precision agriculture. Examined carefully are the parameters that are likely to affect the construction and design of lecture halls and other educational spaces, as well as the selection of proper audio-visual systems. Thoroughly analysed are various factors including the design specifications for contemporary educational technology, which are subsequently reviewed in relation to the potential design alternatives within the existing space.